The Effect of Local Excellence-Based Comic Media on Conceptual Understanding and Environmental Care Attitudes of Islamic Boarding School Students of Different Genders - Akhmad Sukri (Postgraduate, University of Mataram, 2023)
Understanding the concept and attitude of environmental care attitudes is necessary for preserving local excellence. This study aims to determine the effect of implementing local excellence-based comic media on the conceptual understanding and environmental care attitude of Islamic boarding school students of a different gender. This research is quasi-experimental, using a one-group pre-test and post-test design. The research was conducted in three Islamic boarding schools, i.e. MTS MT Mamben, SMP IT Putra Ar-Risalah Paok Lombok, and SMP IT Putri Ar-Risalah Paok Lombok, involving 38 female and 30 male students. The research instrument used a test to determine students' conceptual understanding of local excellence and a questionnaire to assess students' environmental care attitudes. Data were analyzed using N-gain, one-way ANOVA, and continued with post hoc tests to determine the effect of implementing comic media in each experimental group. A DIF analysis was carried out on questionnaire items using RASCH to determine students' environmental care attitudes of different genders. The results showed that (a) the implementation of comic media based on local excellence at Islamic boarding schools could increase students' understanding of local excellence (N-gain = 0.44 to 0.60) and increase students' environmental care attitude (N-gain = 0.33 to 0.58), (b) there are differences in concept understanding and environmental care attitude in the experimental group (Sig <.05). These results indicate that there is a relationship between conceptual understanding and students' environmental care attitudes. The higher the conceptual understanding, the higher the students' environmental care attitude, and vice versa, and (c) female students tend to have a better environmental care attitude than male students. However, on the other hand, male students can think logically and rationally, so they tend to care about the causes of damage to local excellence, especially coral reef ecosystems